Time, Freedom and the Self The Cultural Construction of "Free" Time - Shir-Wise, Michelle (Leisure Studies in a Global Era, 2019)
While abundant research has investigated time use, much less attention has been given to the cultural meanings attached to free time and what these may express with regard to conceptions of freedom and the self. In an attempt to fill this gap, Michelle Shir-Wise examines not only what people do in their free time, but also how they perceive, interpret and experience it, and in what way it relates to notions of happiness, freedom and the ideal self. Time, Freedom and the Self draws on contemporary theoretical debates concerning the relation between discourse, cultural repertoires, subjective meaning and agency, as well as literature around the sociology of leisure, to inform a unique interpretation of free time ("disciplined freedom"), developed in the light of in-depth questionnaires and interviews with middle-class, middle-aged participants in suburban Israel.